Functional connectivity in the Reserva Conchal as part of the Corredor Biológico Costero Marino Baulas-Conchal, Costa Rica - Montilla-Rivas, Analy (2025)
Analyzing functional connectivity in fragmented landscapes is essential for maintaining biodiversity; however, such studies in Costa Rica are limited. To address this need, the present research was developed to assess functional connectivity across different land uses within the Reserva Conchal, part of the Baulas-Conchal Coastal Marine Biological Corridor (CBC-BC). The land cover and land use layer from SINAC 2023 was validated, achieving an accuracy of 98.53% and a Kappa index of 0.97. The selected target species were the mantled howler monkey (Alouatta palliata) and the white-tailed deer (Odocoileus virginianus), chosen based on their biological traits to encompass a range of dispersal capacities. Functional connectivity was modeled using spatial graph techniques with the “Graphab” software and habitat suitability index (HSI) analysis with “MaxEnt” in “R”. The global scale metrics indicated a higher probability of connection for O. virginianus (PC = 0,066) compared to A. palliata (PC = 0,0058), suggesting that the white-tailed deer is better adapted to diverse land uses, while the howler monkey exhibited more fragmented habitat patches and a high dependency on specific corridors. Local scale metrics identified key patches and links to improve connectivity for both species. It was concluded that functional connectivity could be improved through restoration and conservation efforts in priority areas, highlighting the need to integrate such methodologies into decision-making strategies for landscape management in the country.